2021
DOI: 10.3389/fcell.2021.665591
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Lipid Peroxidation-Derived Electrophiles in Pathogenesis of Colonic Inflammation and Colon Cancer

Abstract: Redox stress is a common feature of gut disorders such as colonic inflammation (inflammatory bowel disease or IBD) and colorectal cancer (CRC). This leads to increased colonic formation of lipid-derived electrophiles (LDEs) such as 4-hydroxynonenal (4-HNE), malondialdehyde (MDA), trans, trans-2,4-decadienal (tt-DDE), and epoxyketooctadecenoic acid (EKODE). Recent research by us and others support that treatment with LDEs increases the severity of colitis and exacerbates the development of colon tumorigenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 91 publications
3
21
0
Order By: Relevance
“…Indeed, our recent analysis of the Cancer Genome Atlas (TCGA) database showed that compared with healthy controls, the expression of a series of protective and antioxidant genes are signi cantly reduced in human colorectal tumor samples 24 , suggesting a dysfunctional antioxidant defense system in colorectal cancer patients. A similar dysfunctional antioxidant system is also observed in IBD 23 . Based on our ndings, the individuals with or prone to IBD and/or colorectal cancer could be susceptible to the adverse effects of oxidized LA, and these high-risk individuals may need to reduce the consumption of food products containing high levels of oxidized LA, though further studies are needed before dietary recommendations could be established.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Indeed, our recent analysis of the Cancer Genome Atlas (TCGA) database showed that compared with healthy controls, the expression of a series of protective and antioxidant genes are signi cantly reduced in human colorectal tumor samples 24 , suggesting a dysfunctional antioxidant defense system in colorectal cancer patients. A similar dysfunctional antioxidant system is also observed in IBD 23 . Based on our ndings, the individuals with or prone to IBD and/or colorectal cancer could be susceptible to the adverse effects of oxidized LA, and these high-risk individuals may need to reduce the consumption of food products containing high levels of oxidized LA, though further studies are needed before dietary recommendations could be established.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have also shown that oxidized LA had little effect to initiate diseases: Nolen et al treated healthy rats with frying oils, which contain high levels of oxidized LA, and found no pathological disorders in the treated animals after a 2-year treatment 22 . This could be, at least in part, because the mammalian system has an array of protective and antioxidant mechanisms to counteract the potential detrimental effects of lipid oxidationderived molecules; in contrast, the individuals with or prone to IBD and/or colorectal cancer have a compromised antioxidant defense system and therefore could be susceptible to the adverse effects of oxidized LA 23 . Indeed, our recent analysis of the Cancer Genome Atlas (TCGA) database showed that compared with healthy controls, the expression of a series of protective and antioxidant genes are signi cantly reduced in human colorectal tumor samples 24 , suggesting a dysfunctional antioxidant defense system in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The concept that disbalance between electrophilic and nucleophilic tone encourages initiation and propagation, and delays the termination step of lipid peroxidation is central to most theories of oxidative stress-induced pathophysiological states (at least those predominantly defined by the excess of electrophiles [66,67]) and accumulation of lipid peroxidation end products is evident in many pathological states including those affecting the gastrointestinal tract (e.g. reflux esophagitis, gastritis, gastric ulcers and H.pylori infection, and inflammatory bowel disease [31,[68][69][70]).…”
Section: Discussionmentioning
confidence: 99%
“…The role of HNE in the development of neoplastic cells was mentioned above. Besides, the evidence suggesting a role for HNE in the pathogenesis of many types of cancer also has been reviewed in many papers [ 57 , 58 , 59 , 60 , 61 ]. It is known that in pathological conditions elevated levels of HNE-modified molecules are found in the blood and other tissues.…”
Section: Hne In Pathologymentioning
confidence: 99%